2019
DOI: 10.1016/j.foodres.2018.10.022
|View full text |Cite
|
Sign up to set email alerts
|

What kind of coffee do you drink? An investigation on effects of eight different extraction methods

Abstract: The chemical composition of brewed coffee depends on numerous factors: the beans, post-harvest processing and, finally, the extraction method. In recent decades, numerous coffee-based beverages, obtained using different extraction techniques have entered the market. This study characterizes and compares eight extraction coffee methods from a chemical-physical point of view, starting from the same raw material. Specifically, three types of Espresso, Moka, French Press, and 3 filter coffee that for the first tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
93
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 32 publications
9
93
1
9
Order By: Relevance
“…These findings are supported by a number of previously published findings that suggested that caffeine amount depends on the preparation and extraction of the beans (2,24). Furthermore, Angeloni et al, reported that the chemical composition of brewed coffee depends on numerous factors: the beans, post-harvest processing and, finally, the extraction method (31). Interestingly, there was no difference between the amount of caffeine recovered from instant coffee and that of energy drinks and that regardless of preparation methodology used, coffee beans (black, brown or green) were shown to have significantly more caffeine contents than energy drinks (Figure 4).…”
Section: Resultssupporting
confidence: 76%
“…These findings are supported by a number of previously published findings that suggested that caffeine amount depends on the preparation and extraction of the beans (2,24). Furthermore, Angeloni et al, reported that the chemical composition of brewed coffee depends on numerous factors: the beans, post-harvest processing and, finally, the extraction method (31). Interestingly, there was no difference between the amount of caffeine recovered from instant coffee and that of energy drinks and that regardless of preparation methodology used, coffee beans (black, brown or green) were shown to have significantly more caffeine contents than energy drinks (Figure 4).…”
Section: Resultssupporting
confidence: 76%
“…In general, the levels of CGA (including their lactones) in coffee brews as reported in the literature may vary largely, from 26 mg/100 mL (including studies that only reported concentrations of the three main CQA isomers) [28,29] to extreme 1141 mg/100 mL (considering unusually concentrated espresso coffees) [30,31], but common values, including caffeoylquinic, feruloylquinic and dicaffeoylquinic compounds, and their main lactones (1,5-caffeoylquinides), range from 50-200 mg/100 mL [32,33]. Percent distribution of CGA compounds in coffee brew, in order of abundance is, on average: 5-CQA (41%-48%), 4-CQA (20%-25%), 3-CQA (17%-20%), 5-FQA (4%-8%), 4-FQA (2%-5%), 3-FQA (1%-4%), 3,4-diCQA (1%-2.5%), 3,5-diCQA (1%-1,5%), 4,5 (~1%), others (<1%) [33,34].…”
Section: Chlorogenic Acids Levels In Coffee Beverages and Estimated Dmentioning
confidence: 99%
“…In general, considering the different existing brewing methods (Table 1), the values reported for major CGA (CQA, FQA, and diCQA), including the major lactones, in brews prepared at 6%-17.5%, (weight/water volume) using light to dark ground roasted coffees vary as follows: from~25 to 150 mg/100mL in manually dripped (filtered) brews [33,34,40], from~35 to 170 mg/100mL in electric dripper (filtered) brews [33,34,41,42], from~40 to 1000 mg/100 mL in espresso brews [30,[32][33][34]41,42]; from~55 to 150 mg/100 mL in Italian coffee brews prepared by moka pot [32][33][34]41,42]; from~40 to 280 mg/100 mL in French press brews [32,42,43]; about~110-200 mg/100 mL in Turkish coffee brews [29,34], from~70 to 230 mg/100 mL in boiled coffee brews [28,33,34,42]; and approximately 35 to 319 mg/100mL in cold-dripped brews [32,34,43,44].…”
Section: Chlorogenic Acids Levels In Coffee Beverages and Estimated Dmentioning
confidence: 99%
“…A low concentration used in this study (1 mM) corresponds to 0.194 mg/mL caffeine, and 3 mM corresponds to 0.583 mg/mL. Establishing a correlation with caffeine content in diverse coffee types, Angeloni et al 21 observed that three types of expresso contain caffeine ranging from 1.43 to 4.2 mg/mL; a Moka coffee contains 1.28 mg/mL; a French press and a Aeropress coffee contain 0.52 and 0.78 mg/mL, respectively; a cold brew coffee contains 1.25 mg/mL of caffeine.…”
Section: Cell Culturementioning
confidence: 67%